On the Promotion of E-commerce on International Trade- Analysis Based on the Background of Digitalization - Yan, Weili (International Journal of Global Economics and Management, 2024)
With the continuous development of Internet technology, the global economy is getting closer and closer, and e-commerce emerges. As a new way of economic and trade, e-commerce provides an unlimited market platform for international economic and trade, bringing unprecedented opportunities for international trade participants. However, the development of e-commerce is also accompanied by various problems. This article takes the impact of e-commerce on international economic and trade as the starting point, analyzes the positive impact of e-commerce in international trade, explores the challenges brought by it, and give play to the role of Silk Road e-commerce in the background of China's "Belt and Road". Promote the healthy development of international economic and trade.